The Path to Sainthood: Celibacy in Catholicism and Pabbajita in Buddhism - Muammar Saudi (Al-Adyan: Journal of Religious Studies, 2023)
Celibacy is a spiritual act of worship that can be found in Catholicism and Buddhism. Some cases show an inability to continue the spiritual journey of celibacy. This research was conducted to describe the concept of celibacy in Catholicism and Buddhism and its comparison. The explanation and analysis of the central concept of celibacy are based on studies conducted through literature studies. The results of this study indicate: First, celibacy in Catholicism is a choice made by someone not to enter into marriage ties as a form of devotion to God. Meanwhile, in Buddhism, celibacy is one way to achieve peace. Second, the basis for practicing celibacy for Catholics comes from the prohibition of marriage in the Letter of Matthew in a message from Jesus. Whereas in Buddhism, celibacy is a way of life from Pabbajita, what the Buddha taught. Third, the controversy over celibacy in Catholicism began when Peter, the Pope at that time, was married, as well as cases of sexual harassment by priests. Whereas in Buddhism, especially Theravada, the debate is not big because it is a moral code of Pattimokkha given directly from Buddha Siddharta Gautama for those who wish to attain Nibbana. This article argues that celibacy in Catholicism and Buddhism is dynamic and controversial. Selibat adalah tindakan ibadah spiritual yang dapat ditemukan dalam agama Katolik dan Budha. Beberapa kasus menunjukkan ketidakmampuan untuk melanjutkan perjalanan spiritual selibat. Penelitian ini dilakukan untuk mendeskripsikan konsep selibat dalam agama Katolik dan Buddha serta perbandingannya. Penjelasan dan analisis konsep sentral selibat didasarkan pada studi yang dilakukan melalui studi literatur. Hasil penelitian ini menunjukkan: Pertama, selibat dalam agama Katolik adalah pilihan yang dilakukan oleh seseorang untuk tidak melangsungkan ikatan perkawinan sebagai bentuk pengabdian kepada Tuhan. Sedangkan dalam agama Buddha, selibat adalah salah satu cara untuk mencapai kedamaian. Kedua, dasar untuk mempraktikkan selibat bagi umat Katolik berasal dari larangan pernikahan dalam Surat Matius dalam pesan dari Yesus. Sedangkan dalam Buddhisme, selibat adalah cara hidup dan Pabbajita apa yang diajarkan Sang Buddha. Ketiga, kontroversi selibat dalam Katolik dimulai ketika Petrus Paus yang menikah, serta kasus pelecehan seksual oleh para pendeta. Sedangkan dalam agama Buddha, khususnya Theravada, perdebatannya tidak besar karena merupakan kode moral Patimokkha yang diberikan langsung dari Buddha Siddharta Gautama bagi yang ingin pencapaian Nibbana. Artikel ini berpendapat bahwa selibat dalam agama Katolik dan Buddha bersifat dinamis dan kontroversial.